Hubungan Pengetahuan Penggunaan Pembalut dengan Kejadian Pruritus Vulvae Saat Menstruasi Pada Remaja Putri di SMP 3 Majalengka - Iis, Iis; Rohaeni, Ela (Universitas Pahlawan Tuanku Tambusai, 2024)
Irritation of the genitalia (Pruritus vulvae) is a disorder characterized by itching sensations of the female external genitalia. At the time of menstruation, the genital area is so easily infected that frequent changes of pads are required. This study aims to determine the relationship between knowledge of the use of sanitary pads with the incidence of vulvar pruritus in adolescents at SMP 3 Majalengka. The type of research used is quantitative analytics with a cross sectional design. The sample of this study was 84 people with stratified random sampling. The data collection method uses questionnaires that are shared through google forms. The analysis used is univariate and bivariate analysis. The results of the univariate study showed that most had less knowledge, namely as many as 54 respondents (64.3%) and most experienced Pruritus Vulvae, which was as many as 52 respondents (61.9%). Based on the results of bivariate research, it was found that there was a significant relationship between the knowledge of the use of sanitary pads and the incidence of Pruritus Vulvae during menstruation with a p value of 0.032, meaning a p value of < 0.05. Based on the results of the study, it is expected that the principal of SMP 3 Majalengka should work with health workers to provide knowledge about vulvarial pruritus.